2018
DOI: 10.1093/ons/opy196
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned Using a High-Definition 3-Dimensional Exoscope for Spinal Surgery

Abstract: This study demonstrates the feasibility of utilizing the 3D 4K-HD EX system and highlights potential technical assets of this novel technology in regard to optics, ergonomics, and maneuverability. Further clinical research is needed to examine the clinical effectiveness of the EX system for different surgical approaches through quantitative methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 13 publications
4
93
0
Order By: Relevance
“…High-definition (HD) 3D exoscope systems have been utilized in spinal surgeries with comparable results. 5 , 6 We have found that the use of an exoscope to be far more beneficial compared to a traditional microscope in this instance. The model we have utilized is the Modus V (Synaptive Medical, Toronto, Canada).…”
mentioning
confidence: 83%
“…High-definition (HD) 3D exoscope systems have been utilized in spinal surgeries with comparable results. 5 , 6 We have found that the use of an exoscope to be far more beneficial compared to a traditional microscope in this instance. The model we have utilized is the Modus V (Synaptive Medical, Toronto, Canada).…”
mentioning
confidence: 83%
“…AR will also be an important addition when exoscopes are used for spine procedures. 42 Apart from AR displays on monitors, 31 an alternative to HUDor HMD-based AR might be projection systems offering direct augmentation by spatial AR projecting images directly onto the physical object surface without the need to carry or wear any additional display device. 33 Systems providing such an augmentation in the open space would increase the surgeon comfort compared with wearing heavy HMDs for longer procedures and would improve sharing and collaboration during a procedure; however up to now, such systems are not yet available.…”
Section: Smentioning
confidence: 99%
“…It took about nine years to further evolve the 2D visualization and introduce the first 3D exoscopic visualization system [39,40] . In the following years, the 3D exoscope has been used to perform various technical more demanding neurosurgical procedures, even in pediatric cases, including treatment of cerebrovascular disorders (i.e., aneurysm clipping and bypass surgery), degenerative spinal disorders, and resection of cranial and spinal tumors [41][42][43][44][45][46][47][48][49][50] . VITOM®-3D (Video Telescopic Operating Microscope, Karl Storz GmbH & Co. KG, Tuttlingen, Germany), provides a 3D visualization in ultra-high definition (4K) quality, with a focal length of 20-50 mm and magnification ranges from 8× to 30×.…”
Section: Exoscope In Neurosurgerymentioning
confidence: 99%
“…• Need for reposition and refocusing when surgical exposure changed from extradural to intradural Kwan et al [47] 2019 3D Barbagallo et al [44] 2019 3D…”
Section: Spinal Meningioma Surgerymentioning
confidence: 99%